Fluorescence molecular tomography of brain tumors in mice - Deliolanis, Nikolaos C; Ntziachristos, Vasilis (Cold Spring Harbor protocols, 2013)
Fluorescence molecular tomography of tissues is a method that three-dimensionally resolves fluorescence biodistribution in vivo, with applications in small-animal research and pre-clinical diagnostics. There are many alternative imaging geometries in optical tomographic experimental systems, but in general, all imaging setups consist of four subsystems: illumination, animal mount, imaging, and automation and data acquisition (i.e., electronics and computer). Here we refer to charge-coupled device (CCD)-based systems that work in trans-illumination (i.e., illumination and detection occur on opposite sides of the subject), while a mouse or other small animal is rotated through 360° to allow photon acquisition from multiple projections. We present a procedure to tomographically reconstruct the biodistribution of fluorescence in small animals. The imaging system and equipment are described, the step-by-step image acquisition and preliminary image-processing methods are presented, and the tomographic reconstruction procedure is outlined. Finally, the method is showcased by imaging the fluorescence activity of a brain tumor of a glioblastoma mouse model.